HUBUNGAN MOTIVASI BERPRESTASI DAN KEMAMPUAN BERPIKIR KRITIS DENGAN KEMAMPUAN MENULIS NARASI - sri, Sri Wulan Anggraeni (JURNAL PENDIDIKAN DASAR, 2015)
Abstract: The purpose of this study was to determine the relationship of achievement motivation and ability to think critically with ability to write narrative. This study is the correlation was conducted in the public elementary school district subdistrict CibitungÂ  Bekasi. Samples were obtained by simple random sampling technique. The sample size was 100 people with 25 people each at any public elementary school. This study used a survey method with a correlation technique (connectedness). The result show that there is a positive relationship between: (1) achievement motivation with ability to write narrative; (2) ability to think critically with ability to write narrative; (3) achievement motivation and ability to think critically with ability to write narrative. Based on the findings in this study, the authors suggest that educators approached by students using interesting and appropriate learning media so as to enhance the achievment motivation and ability to think critically of students and to facilitate studentsnin writing narrative process activities.Â Keywords: achievement motivation, ability to think critically, ability to write narrativeÂ